The Post-Marcos Regime, The Non-Bourgeois Opposition and the Prospects of a Philippine "October" - Abinales, P.N. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The rebellion that ousted Marcos combined massive civilian support with a military revolt. This gave rise to a reconstituted bourgeois liberal democratic State involving the emergence of new political forces hitherto marginal to the anti-Marcos opposition and the relative isolation of the Philippine Left from the political mainstream. This new political situation is set in a backdrop of economic crisis and bleak prospects for social recovery. The forces committed to social and class-based change remain disunited, and the revolutionary vanguard suffers from a “crisis of imagination” and an inadequate strategy of resistance. The paper argues that the “February Revolution” has only changed the mode of political governance but not necessarily the political economy of the country. The present is only an interregnum which may either slide back to pre-Marcos conditions or create new ones that will facilitate at a future date the occurrence of a Philippine “October”.
Keywords: bourgeois, February Revolution, October Revolution, anti-Marcos opposition, economic crisis, revolutionary vanguard